A Simple and Fast Synthetic Pathway of b-Enamino-Esters by Condensation of b-Keto Ester with Aliphatic and Aromatic Amines in Ethanol - Kouadri, Y.; Ouahrani, M.R.; Missaoui, B.E.; Chebrouk, F.; Gherraf, N. (Asian Journal of Chemistry, 2015)
The b-keto ester undergoes condensation reactions with aliphatic and aromatic amines in ethanol to give high-yielding b-enamino ester. The method is simple, cost-effective and environmentally benign. Structural characterization of the synthesized compounds was carried out by spectroscopic methods (1H NMR, 13C NMR and DEPT).